SAT0471 EFFECTS OF ONE YEAR TOFACITINIB THERAPY ON BONE DENSITY AND BIOMARKERS OF BONE TURNOVER IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Hamar, A.; Pusztai, A.; Végh, E.; Horváth, Á.; Szamosi, S.; Pethö, Z.; Szántó, S.; Szücs, G.; Bhattoa, H. P.; Tajti, G.; Panyi, G.; Hodosi, K.; et al.
Abstract : Background: Oral JAK inhibitor, tofacitinib appeared as a new therapeutic option, beside biological therapies, which has already proven its safety and effectivity in RA, but we lack of knowledge how it affects density of bone structures and bone turnover markers. Objectives: The aim of this study was to assess the effects of one-year tofacitinib therapy on bone metabolism in patients with RA. Methods: Altogether 30 RA patients with active disease were recruited and treated with tofacitinib in this 12-months follow-up study. Mean age of patients were 52.8±10.0 years, duration of rheumatoid arthritis were 7.7±5.0 years. Half of the patients haven't received biological treatment prior tofacitinib therapy, other half of the patients switched to tofacitinib therapy after completing washout. 15 patients received 2x5mg and 15 patients received 2x10mg tofacitinib daily for 12 months. On both arms 2-2 patients have discontinued treatment and excluded from the study. Assessments were performed at baseline, month 6 and 12. Levels of CRP and IgM rheumatoid factor (RF) antibodies were measured by quantitaive nephelometry and levels of anti-CCP, sclerostin, osteocalcin (OC), P1NP were assesed by ELISA. Bone density was assesed by DXA (dual-energy X-ray absorptiometry, Lunar) and pQCT imaging techniques. Levels of DKK-1, OPG, RANKL were measured by multiplex microbead immunoassay (BioLegend LEGENDplex). In addition, disease activity (DAS28), age and disease duration were also measured. Correlations were determined by Spearman's analysis. Univariate and multiple regression analysis using the stepwise method was applied to investigate independent associations between DXA measurements (dependent variables) and laboratory parameters (independent variables). Results: Tofacitinib significantly reduced DAS28 (p<0.001) and HAQ values (p=0.001), also level of CRP (p<0.001) and We (p=0.014). With respect to bone biomarkers we have experienced significant increase in levels of OC (p=0.013), OPG (p=0.006), sclerostin (p=0.026) and vitamin-D (p=0.017) at month 6, also in levels of OPG and vitamin-D (p=0.004, p=0.003) at month 12. We have found decrease in levels of CTX at month 6 (p=0.009) and 12 (p=0.003). When we examined the groups separately, we've found significant increase in levels of P1NP (p=0.027, p=0.005), OPG (p=0.005, p=0.002) and vitamin-D (p=0.001, p=0.004) at month 6 and 12, also in OC at month 6 (p=0.027) in Group A (2x5mg). In Group B (2x10mg) we've experienced a significant decrease in levels of phosphate and CTX at month 6 and 12 (p=0.012, p=0.021, and p=0.005, p=0.007). Conclusion: One year tofacitinib treatment effectively stabilized bone density in patients with rheumatoid arthritis, and led to the increase of bone turnover markers, which is beneficial for ossification in long term. Acknowledgments: This research was supported by an investigator-initiated research grant from Pfizer. Disclosure of Interests: Attila Hamar: None declared, Anita Pusztai: None declared, Edit Végh: None declared, Ágnes Horváth: None declared, Szilvia Szamosi: None declared, Zsófia Pethö: None declared, Sándor Szántó: None declared, Gabriella Szücs: None declared, Harjit Pal Bhattoa: None declared, Gábor Tajti: None declared, György Panyi: None declared, Katalin Hodosi: None declared, Zoltán Szekanecz Grant/research support from: Pfizer, UCB, Consultant of: Sanofi, MSD, Abbvie, Pfizer, Roche, Novertis, Lilly, Gedeon Richter, Amgen